Demographic, clinico-pathological features and management pattern of primary bone tumors in a tertiary care hospital of South India - Shanmugam, Subbiah; Susikar, Sujay; T., Bharanidharan; Jebasingh, Arun Victor (International Journal of Research in Orthopaedics, 2021)
Background: Primary bone tumors are very rare tumors. The true incidence of bone tumors is not well established and is under reported due to rarity and lack of accurate registries. Hence it is essential to study about the demographic, clinico-pathological features and the pattern of surgical management of bone tumors. The aim of this study is to analyze the demographic and clinico-pathological features of primary bone tumors that were managed by surgery. Methods: A retrospective analysis of all patients with primary bone tumor who were treated by surgery from 2012 to 2019 was done. The age, sex distribution, histopathology, location of the tumor and surgical procedure done were analyzed. Results: Among 103 patients analyzed, 66 (64%) were men and 37 (36%) were women. Primary bone tumors most commonly presented in 11 to 20 years of age with 35 (33.9%) patients occurring in this age group. Osteosarcoma was the most common primary bone tumor and it occurred in 49 (47.6%) patients, out of which 34 (69.3%) patients were below 20 years of age. Giant cell tumor was the most common benign bone tumor and it occurred in 22 patients, out of which nine (40.9%) patients were of age 21 to 30 years. Distal femur was the most common site with 39 (37.9%) patients. The limb preservation rate for malignant appendicular bone tumors was 69.0%. Conclusions: The diagnosis of bone tumor depends not only on histopathological features but also needs correlation with age, clinical features, tumor location and radiological features for confirmation of diagnosis.